Wymogi ostrożnościowe dotyczące nadzoru bankowego na poziomie ponadnarodowym w aspekcie kontroli banków - Niewiadoma, Maria (Requirements for Effective Banking Supervision on the Supranational Level in the Process of the Banks Control, 2006)
The process of harmonization the banking system on the international market is connected with the role of the banking supervision. The core principles for effective banking supervision have been worked out by the Basel Committee on Banking Supervision and Principles 6-15 which refer to regulations and requirement. The most important is Principle 6 refering to the capital adequacy and Principle 14 about the internal control mechanism. Supranational requirements have been the base for the national principles which are elaborated as internal banking law in Poland.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (4); 2006; nr 1119, s. 187-195